(untitled) (Window of Public Health Journal, 2025)
Supplementary Feeding (PMT) is an intervention program implemented by the government in the toddler age group, which is intended as additional intake besides daily staple foods to overcome the problem of malnutrition. This study aimed to determine the effectiveness of the supplementary feeding (PMT) program for malnourished toddlers with an input-process-output approach at the Tamalanrea Jaya Community Health Center. The type of research used was quantitative descriptive. Hypothesis testing was carried out using the Chi-Square test. The instrument used was a questionnaire. The research sample was 50 people. The results of the study showed a relationship between human resources and the effectiveness of the PMT program (ρ = 0.000), there was a relationship between facilities and infrastructure and the effectiveness of the PMT program (ρ = 0.002), there was a relationship between program implementation and the effectiveness of the PMT program (ρ = 0.023) and there was a relationship between program achievements and the effectiveness of the PMT program (ρ = 0.001). These findings suggest that future research should focus on these areas to enhance the PMT program’s effectiveness further. It is hoped that future researchers can analyze the effectiveness of the supplementary feeding program for toddlers in more depth.